2016
DOI: 10.1155/2016/4163094
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Expression and Function of Immunoglobulin-Like Transcript 4 (ILT4, LILRB2) in Dendritic Cells from Patients with Systemic Lupus Erythematosus

Abstract: Dendritic cells (DC) play an important role in the development and maintenance of immune tolerance. Although the inhibitory receptor ILT4/LILRB2 has been related with the tolerogenic phenotype of DC, the possible role of this receptor in the breakdown of DC tolerogenic function in systemic lupus erythematosus (SLE) has not been elucidated. In this study, we analyzed the expression and function of the inhibitory receptor ILT4 in DC from SLE patients. We found that the percentage of ILT4 positive plasmacytoid DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…The relative lack of variation in endometrial ILT4 + DCs from both healthy individuals and patients with RM and RIF highlights the homeostasis of immunological environment in this tissue.Consistent with our results, the level of ILT4 + pDC from patients with systemic lupus erythematosus (SLE), which is a chronic systemic autoimmune disease, also showed a high variability with percentages varying from 8.1% to 68.8% 36. Taken together, our results represent a new concept for the establishment of immune tolerance in human pregnancy.The large variations in peripheral blood ILT4 + DCs among individuals are thought to be due in part to other aspects of human conditions.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The relative lack of variation in endometrial ILT4 + DCs from both healthy individuals and patients with RM and RIF highlights the homeostasis of immunological environment in this tissue.Consistent with our results, the level of ILT4 + pDC from patients with systemic lupus erythematosus (SLE), which is a chronic systemic autoimmune disease, also showed a high variability with percentages varying from 8.1% to 68.8% 36. Taken together, our results represent a new concept for the establishment of immune tolerance in human pregnancy.The large variations in peripheral blood ILT4 + DCs among individuals are thought to be due in part to other aspects of human conditions.…”
supporting
confidence: 89%
“…Although increased percentage of tolerogenic DCs in pregnancy was recently described, 14 Consistent with our results, the level of ILT4 + pDC from patients with systemic lupus erythematosus (SLE), which is a chronic systemic autoimmune disease, also showed a high variability with percentages varying from 8.1% to 68.8%. 36 Thus, although there is magnitude of normal variation, our data provide support for the feasibility of using ILT4 + DCs as a basis for detection of RM and RIF.…”
Section: Discussionsupporting
confidence: 53%
“…Human leukocyte antigen-G (HLA-G) is a class I non-classical HLA molecule that plays an important regulatory role in the immune system during viral infections and some autoimmune diseases [213]. Paola Del Carmen Guerra-De-Blas et al reported that significantly lower levels of ILT4-positive circulating pDCs and cDCs were detected in SLE patients; this diminished expression of ILT4 may contribute to a higher immunogenic phenotype of DCs in SLE [214]. It has also been reported that monocytes from psoriatic arthritis patients reveal downregulated expression of ILT4, demonstrating that alterations of these inhibitory receptors may not be exclusive to SLE patients but, rather, a common characteristic that SLE shares with other autoimmune conditions [215].…”
Section: Co-signaling Axes In Dendritic Cells (Dcs) Relating To Slementioning
confidence: 99%
“…Up to now, numerous researchers reported that the presence of HLA-G in numerous cancer types, including NSCLC and leukemia, is correlated with poor prognosis (15-17). ILT4/HLA-G has been investigated as an inhibitory axis in simian immunodeficiency virus and human immunodeficiency virus infections, recurrent implantation failure and systemic lupus erythematosus (18-20). In a previous study, the co expression of ILT4/HLA-G in NSCLC and its correlation with a reduced overall survival (OS) time in patients with NSCLC was revealed, and also its activation of extracellular signal regulated kinase (ERK) signaling was demonstrated.…”
Section: Introductionmentioning
confidence: 99%